Building business process ontology based on concept hierarchy model. (2017) - Huang, Ying; He, Xianwen
The agility and efficiency of business processes have great influence on the company's competitiveness. However, current detection of business process management system reveals the problem that it does not satisfy the customer requirements, because there is a lack of sufficient semantic information between business process. This paper proposes an approach for ontology extraction on business process by incorporating concept hierarchy as background knowledge. Incorporating the background knowledge in procedure of the process ontology has two main advantages: 1) background knowledge accelerates the building process, thereby minimising the conversion cost; 2) background knowledge guides the extraction of knowledge, which hides in database. To validate the method given in this paper, we use part of the sales order processes from SAP reference process models to construct business process ontology. The gold standard experiments show using this method can correct an effective construct process ontology.